Peran Psikologi Manajemen dalam Optimalisasi Motivasi Guru sebagai Strategi Peningkatan Efektivitas Sekolah - Misbahul Ulum; Dina Salsabila; Sabila Sherinata Mayandari; Muhammad Farhan Firdaus; Muhammad Yusrizal Lifanto; Mu’alimin Mu’alimin (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the role of management psychology in optimizing teacher motivation as a strategy to improve school effectiveness. Teacher motivation is a major determinant in achieving educational goals, but is often constrained by factors such as excessive workload, lack of appreciation, and an unsupportive work environment. Through a literature review approach, this study examines various previous studies to identify effective management psychology strategies in improving teacher motivation, such as providing support, recognition, training, and good communication. The results of the study indicate that high teacher motivation has a significant impact on their performance, learning effectiveness, and student achievement. In addition, inspirational leadership and a collaborative work environment also play an important role in encouraging teacher motivation. Thus, the application of management psychology principles can create a more effective and competitive education system.